Diversity, Geographical Habitat Usage and Distribution Assessment of Flies (Insecta: Diptera) in Nilgiri Hills, Tamil Nadu, India - Moinudheen, N; Samson, Arockianathan (International Research Journal of Insect Sciences, 2022)
In the study of diptera diversity and distribuiton conducted in 2020-2021 we found insect species in 23 families out of 64 common individual species. Site-A Hidden Valley is considered to be the place with the highest number of individual (861nos). In this study we found that most pollination in the Nilgiris in the diptera order is done on small flowering plants. Fruit fly insect are never harmful to the fruits of the Nilgiris eg- Rhagoletis sp. Stomoxys sp, Musca sp species of insect found mostly in cattle and gaur in the Nilgiris The study was conducted in four different forest areas in the Nilgiris and in the lake area, Ooty Lake is the most associated area for humans and flies. This study is not only about this period but also about the future studies of these insects mostly because they are important for all types of ecological environment.